The effects of resisted training using parachute on sprint performance - Smirniotou, A.; Martinopoulou, K.; Argeitaki, P.; Paradisis, G.; Katsikas, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Running velocity is an important element of successful performance in many sports. Two important factors that affect running velocity are stride length and stride frequency (Mero et al, 1992). Research has shown that running velocity is improved using repetitive sprint training and strength training (Delecluse et al., 1995). The means utilized in sprint training with pull against resistance are sled and parachute sprinting. The purpose of this study was to examine the effects of resisted (using parachute) and un-resisted sprint training programs on acceleration and maximum speed performance. Methods 16 sprint athletes (12 male, 4 female), age 25±4 years, completed a resisted (n=8) and an un-resisted (n=8) sprint training program. The resisted group followed the program towing a large size chute and the un-resisted group followed a similar sprint training program without resistance. The training program consisted of 4x30m and 4x50m maximal runs and was applied 3 times/week for 4 weeks. All subjects performed a 50m run and the running velocity of 0-10m, 10-20m, 20-40m and 40-50m was measured. In addition, stride length, stride rate, contact time and flight time were evaluated between the 1-7m during the acceleration phase and between 40-47m during the maximum speed phase. A series of ANOVA was used separately for acceleration and maximum speed phases. Results- Discussion The resisted sprint training group improved running velocity in all sections of acceleration phase 0-10m, 10-20m and 0-20m, while un-resisted sprint training group in the run section 0-20m. Comparison between groups indicated that running velocity was significantly higher during run section 0-20m in the resisted group compared to the un-resisted group (F1, 12=5.307, p=0.04). For the maximum speed phase the resisted sprint training program improved running velocity in the 40-50m run section and the maximum running velocity between 40-47m, while un-resisted sprint training had no effect in any run section in the maximum speed phase. Stride length increased after resisted and un-resisted sprint training in acceleration phase, whereas stride rate increased only after resisted sprint training in maximum speed phase. Resisted sprint training with a large size chute for 4 weeks significantly improves running velocity during acceleration phase by increasing stride length and during maximum speed phase by increasing stride rate in sprint athletes. References Delecluse C, Van Coopenolle H, Willems E, Van Leemputte M, Diels R, Coris M (1995). Influence of high-resistance and high velocity training on sprint performance. Medicine and Science in Sports and Exercise, 27(8), 1203-1209. Mero A, Komi PV, Gregor RJ (1992). Biomechanics of sprinting: A review. Sports Medicine, 13, 376-392.